Optimizing renewable energy systems for water security: a comparative study of reanalysis models (2024)
The current global scenario of unequal access to water and electricity motivates the search for solutions based on available resources, such as renewable energies and desalination. Additionally, adequate sizing of renewables requires extensive and reliable time series, which are usually unavailable. Reanalysis models are an option to consider, but only after evaluating their local accuracy, generally through performance metrics. This study evaluated the performance of the solar radiation, temperature, and wind speed products from MERRA2 and ERA5-Land in comparison to ground data, as well as their influence on the optimal initial configuration of a renewable energy system for desalination in La Guajira, Colombia. HOMER Pro was the software tool employed to establish the best arrangements for the resulting renewable power systems, and the study included a sensitivity analysis considering different annual capacity shortages, operating hours, and energy needs for desalting. ERA5-Land performed better than MERRA2 in matching the time series from the local station. The relative error of the cost of electricity of systems dimensioned from reanalysis was less than 3% compared to systems from ground measurements, with a renewable fraction above 98%. For the study area, ERA5-Land reanalysis represents a reliable alternative to address the scarcity of solar resource records, but both reanalyses failed to reproduce the wind speed regime.